Low complexity signal detection algorithm for MIMO-OFDM systems - Li, X; Cao, X (Electronics letters, 2005)
In this paper, a very low complexity algorithm for ordering based on the MMSE criterion and detecting based on the QR decomposition of sorted channel matrix in BLAST architectures is presented. The algorithm needs only a fraction of computational effort compared to the standard ordering MMSE algorithm and achieves suboptimal performance.